2023
DOI: 10.3389/fgene.2022.1012706
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy, lipid metabolism, and neurodegenerative pathology by heparan sulfate proteoglycans

Abstract: Heparan sulfate modified proteins or proteoglycans (HSPGs) are an abundant class of cell surface and extracellular matrix molecules. They serve important co-receptor functions in the regulation of signaling as well as membrane trafficking. Many of these activities directly affect processes associated with neurodegeneration including uptake and export of Tau protein, disposition of Amyloid Precursor Protein-derived peptides, and regulation of autophagy. In this review we focus on the impact of HSPGs on autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…A number of findings over the years have implicated heparan sulfate modified proteins in AD pathogenesis 15,63 . Recently, a dramatic example was reported for a member of a large kindred with a dominant disease-causing mutation in PSEN1 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of findings over the years have implicated heparan sulfate modified proteins in AD pathogenesis 15,63 . Recently, a dramatic example was reported for a member of a large kindred with a dominant disease-causing mutation in PSEN1 11 .…”
Section: Discussionmentioning
confidence: 99%
“…HSPGs are known to affect signaling via PI3kinase, Akt, and MAPK systems 13,14 . HSPGs regulate Wnt, Hh, FGF, and BMP signaling during development and play a role in both endocytosis and exocytosis of a variety of molecules [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genetic studies have clearly shown an important role for glypicans in developmental morphogenesis and patterning events. 39 , 40 In vivo evidence indicates that the main function of membrane-attached glypicans is to act as growth factor co-receptors including Wnt signaling (see previous text), Hedgehogs ( Hh ), vascular and fibroblast growth factors (VEGFA and FGF2), and bone morphogenetic proteins (BMPs). Glypicans have been implicated in the pathogenesis of several types of cancer, notably hepatocellular carcinomas, and as potential biomarkers and potential targets for personalized therapy.…”
Section: Cell Surface Gpi-anchored Proteoglycans: the Glypican Familymentioning
confidence: 99%
“…Several excellent reviews on extracellular and cell surface HS–PGs exist in the literature. The interested reader is referred to these for further information [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 ]. In this review, the more important aspects of HS interactive components with representative examples of HS–PGs, such as perlecan and the syndecan, will be covered.…”
Section: Hs Interactive Proteinsmentioning
confidence: 99%